Improving the Functional and Sensory Properties of Cookies by Ultrasonic Treatment of Whey Proteins - Taha Rababah; Muhammad Al-U’datt; Majdi Al-Mahasneh; Ahmad Alsaad; Sana Gammoh; Hana’a Mahili; Khaled Bny Abdhamead; Ali Almajwal; Tha’er Ajouly; Vaida Bartkute-Norkuniene (Journal of Food Quality)
The profiles of food products are one interesting link that adds a new functional component. Cookies became one of the remarkable foods as a result of their simple preparation, a protracted period, and a sensible acceptance by the population. The effects of sonication on physical and sensory characteristics of cookies to be enhanced were studied. The results showed that cookies prepared with 5 and 10% replacement of sonicated whey protein had significant differences in sensory evaluation especially crumb, but there were no significant differences in the physical characteristics, so we can conclude that sonication will improve sensory properties of cookies. Also, we can conclude that biscuit samples supplemented with 5 or 10% WPC were nutrient-rich. The results of the sensory evaluation showed that the cookie samples supplemented with 5% WPC performed better in most of the characteristics but decreased with an increase in the WPC level. The texture properties of the cookie samples indicated that the control cookies with WPC-supplemented cookies showed no significant differences in most studied properties. It can be concluded that the addition of sonicated whey protein enhanced the physiochemical and sensory properties of cookies.